Prolonged and Enhanced Protection Against Corrosion Over Titanium Oxide-Coated 304L Stainless Steels Having Been Irradiated With Ultraviolet - Sathasivam, Kamalasekaran; Wang, Mei-Ya; Anbalagan, Aswin kumar; Lee, Chih-Hao; Yeh, Tsung-Kuang (Frontiers in Materials, 2022)
Austenitic stainless steels are commonly used as the base material for dry-storage canisters in nuclear power plants because of their excellent corrosion resistance and mechanical properties. Dry-storage canisters are often exposed to chloride containing atmosphere near seashores that could induce localized stress corrosion cracking in these stainless steels near the welded regions. Titanium dioxide (TiO2) coatings applied on stainless steel substrates (e.g. Type 304L stainless steels) along with ultraviolet (UV) irradiation have been proposed as a mitigation measures against corrosion in canister materials. In this study, specifically treated TiO2 coatings were applied on stainless steel samples using a dip-coating method. The coated samples were then thermally treated at different annealing temperatures. Corrosion behavior and photocatalytic responses of the coated samples with and without UV illumination was evaluated by electrochemical polarization analyses and open-circuit potential measurements. Surface morphologies of the samples and the crystal structures were studied by scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX) and X-ray diffraction (XRD). It was found that the TiO2 coating not only showed markedly enhanced photo-cathodic protection on Type 304L stainless steels during UV illumination, but could also maintain more active open circuit potentials for several hours after the cutoff of UV. Results from electrochemical polarization analyses further supported the superior corrosion resistance of the coated samples under UV illumination. More importantly, the specifically processed TiO2 coatings applied on the samples, once irradiated with UV, would exhibit a prolonged corrosion resistance that could last for hours in the absence of UV.